Effect of Rhizobium Isolates on Isoflavonoid Levels in Chickpea Plants Infected with Fusarium oxysporum f.sp. ciceris - Arfaoui, A.; Sifi, B.; Boudabous, A.; El Hadrami, I.; Chérif, M. (Phytopathologia Mediterranea, 2006)
The aim of the present studies was to determine the effect of two biocontrol agents, belonging to the genus Rhizobium, PchDMS and Pch43, on the accumulation of soluble phenolic compounds, and particularly constitutive isoflavonoids, in chickpea roots infected with Fusarium oxysporum f. sp. ciceris (Foc), the causal agent of Fusarium wilt of chickpea. Pretreatment of roots with the bacterial isolates before challenge with Foc significantly increased levels of soluble phenolic compounds in both the susceptible ILC482 and the moderately resistant INRAT87/ 1 chickpea cultivars. High performance liquid chromatography analysis revealed the isoflavones biochanin A and formononetin in the chickpea roots, in both the free and the glycosidically bound forms. Bacterization of the roots with Rhizobium isolates before challenge with Foc increased levels of these isoflavones in plant roots. The antifungal activity of crude phenolics extracted from the chickpea roots was tested in vitro on PDA amended with various concentrations of these extracts and inoculated with Foc. Crude phenolics significantly reduced fungal growth and caused considerable morphological changes in the mycelium, including marked cellular disorganization.